Surrogate strains of human pathogens for field release. Issue 1 (1st January 2018) - Park, Sangjin; Kim, Chang-Hwan; Jeong, Seong Tae; Lee, Sang Yup
ABSTRACT: Surrogate microorganisms, in short surrogates, are an essential part of pathogen research. Compared to surrogates used in controlled laboratory environments, surrogates for field release are restricted by concerns about human and environmental safety. For field research of food-borne pathogens, strains of an attenuated pathogen or strains of genetically close non-pathogenic species have been used as surrogates. Genetic modification is usually performed to attenuate virulence, through for examples deletion of genes of virulence and transcriptional regulators and removal of virulence plasmids, and to facilitate detection and monitoring through observing antibiotic resistance, fluorescence, and bioluminescence. For field research of a biological warfare agent Bacillus anthracis, strains of genetically close non-pathogenic species or strains of genetically distant non-pathogenic species have been used, mostly without any genetic modification. Recently, we constructed strains of Bacillus thuringiensis as surrogates for B. anthracis, demonstrating that strain engineering could significantly enhance the utility of surrogates, and that the application of a simple genetic circuit could significantly impact surrogate safety. Thus far, enormous potential of biotechnology has not been exploited enough due to safety concerns regarding the field release of genetically engineered microorganisms. However, synthetic biology is rapidly developing, providing new concepts for biocontainment as well as ingenious genetic circuits and devices, which should be applied in future research of field-use surrogates.